Governance of professional service firms: A configurational approach - Dirk Harlacher; Markus Reihlen (Business Research, 2014)
Professional service firms (PSFs) such as accounting firms, management consultancies, or advertising agencies use very different forms of governance ranging from traditional professional partnerships to public corporations. In spite of the extensive literature, little academic work has been done to synthesize the wealth of theoretical and empirical work on PSF governance into a more comprehensive theory of PSF governance. Taking configuration theory as our theoretical approach, we identify three classes of design parameter (legal form, organizational governance structure, and the systems for managing professionals) and six contingency factors (service commoditization, service diversification, firm size, capital intensity, firm culture, and risk of litigation) that are synthesized into four configurations of PSF governance. These are described, respectively, as the founder-dominated, the collegial, the managerial, and the entrepreneurial configuration.
Keywords: G34; L84; 330; Professional service firms; Governance; Professional partnership; Public corporation; Configuration theory; Archetype theory